The spatial diffusion of geography: A bibliometric analysis of ECTQG conferences (1978-2013) - Sylvain Cuyala (Unité Mixte de Recherche 8504 Géographie-cités, 2016)
This work analyzes the development and diffusion of French-speaking European theoretical and quantitative geography, based on the hypothesis that this movement consisted in three phases (emergence, expansion and diversification). Two datasets serve the analysis; first, a list of presentations at the European Colloquia on Theoretical and Quantitative Geography (ecTQG) over the period 1978-2013; and second, about 55 interviews of geographers involved in this movement. We analyze jointly the frequency of presentations and the spatial network of collaborations based on authors’ institutional affiliation. Main results point to a transition from intra-laboratory collaborations to the emergence of inter-site collaborations, which later became international.